Inflation, capital markets and household saving in Nordic countries - Erkki Koskela; Matti Virén (Bank of Finland, 1992)
Household saving ratios in the Nordie eountries are very low by intemational standards and have declined markedly during the 1980s. Aggregate quarterly time-series data for the period 1970-1989 are used to study the development of household saving behavior over time. The evidenee suggests that the household saving ratio responds positively to both the infiation rate and real ineome growth. There is also some weak evidenee to support the view that the rate of ehange in real housing priees has a negative effeet on household saving ratios.
URN:NBN:fi:bof-201808021842
Keywords: 330